Prevalence and risk factors of postpartum depression at a tertiary care institute - Sivapragasam, Vanithamani; Manjappa, Anitha A.; Patil, Aruna B.; Kalaimani, Monicka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Up to 85% of the women experience some type of mood disturbance in the postnatal period. Postpartum depression affects bonding with infant which may lead to malnutrition and other complications in the infant. This article focuses on the prevalence of depression among postnatal women attending a tertiary care institute in Chennai and to identify the risk factors that affect postpartum depression. Methods: This study was a cross sectional study, performed over a period of three months from January 2019 to March 2019. 200 postnatal mothers were recruited for the study, who were in postpartum period from 1 to 6 weeks after delivery. Specially designed proforma was used to record various determinants to assess the risk factors which could contribute to postpartum depression. The Edinburgh Postnatal Depression Scale was used to detect the depressive symptoms in postnatal mother. Results: A total of 200 cases were studied. Prevalence of postpartum depression was found to be 25%. Primi gravida, history of miscarriage and unplanned pregnancy were associated with increased risk of developing depression in the postnatal period. Fear regarding gender of the child and failure of lactation were not contributing risk factors to postpartum depression. Spacious house and partner support were found to be protective factors to combat depression in postnatal women. Conclusions: Prevalence of postpartum depression was 25%. Significant association was found between primi gravida, history of miscarriage, unplanned pregnancy and postpartum depression. Early screening of the women will reduce the adverse outcomes among both mother and the child.